Cyclosporine A promotes the therapeutic effect of mesenchymal stem cells on transplantation reaction - Hajkova, Michaela; Jaburek, Filip; Porubska, Bianka; Bohacova, Pavla; Holan, Vladimir; Krulova, Magdalena (Clinical science (London, England, 2019)
The successful application of mesenchymal stem cells (MSCs) remains a major challenge in stem cell therapy. Currently, several in vitro studies have indicated potentially beneficial interactions of MSCs with immunosuppressive drugs. These interactions can be even more complex in vivo, and it is in this setting that we investigate the effect of MSCs in combination with Cyclosporine A (CsA) on transplantation reaction and allogeneic cell survival. Using an in vivo mouse model, we found that CsA significantly promoted the survival of MSCs in various organs and tissues of the recipients. In addition, compared to treatment with CsA or MSCs alone, the survival of transplanted allogeneic cells was significantly improved after the combined application of MSCs with CsA. We further observed that the combinatory treatment suppressed immune response to the alloantigen challenge and modulated the immune balance by harnessing proinflammatory CD4+T-bet+ and CD4+RORγt+ cell subsets. These changes were accompanied by a significant decrease in IL-17 production along with an elevated level of IL-10. Co-cultivation of purified naive CD4+ cells with peritoneal macrophages isolated from mice treated with MSCs and CsA revealed that MSC-educated macrophages play an important role in the immunomodulatory effect observed on distinct T-cell subpopulations. Taken together, our findings suggest that CsA promotes MSC survival in vivo and that the therapeutic efficacy of the combination of MSCs with CsA is superior to each monotherapy. This combinatory treatment thus represents a promising approach to reducing immunosuppressant dosage while maintaining or even improving the outcome of therapy.
Keywords: immunomodulation; Drug Evaluation, Preclinical; T-cells; preklinické hodnocení léčiv; rejection; T-Lymphocytes; Cyclosporine A; Mesenchymal Stem Cell Transplantation; cytokiny; Female; přežívání štěpu; myši inbrední BALB C; alografty; zvířata; myši inbrední C57BL; imunosupresiva; Immunosuppressive Agents; cyklosporin; transplantace mezenchymálních kmenových buněk; ženské pohlaví; Male; mesenchymal stem cell; Mice, Inbred C57BL; Cytokines; Allografts; T-lymfocyty; Cyclosporine; Animals; mužské pohlaví; Graft Survival; Mice, Inbred BALB C